THE TECHNOLOGY IMPROVING OF FORMATION OF MULTI-GROUP STRUCTURES - Bobrovskkyi, V. I.; Skovron, I. Ya. (Science and Transport Progress, 2007)
There was suggested the simulating model of the multi-group trains make up process. This model can be recommended for operative control of the station operation. This model allows to find the optimal method and scheme of the making up the specific train, considering the existing quantity of the tracks, and create the plan of the shunting operations.